Biogas production : development of a biogas station in the infrastructure of Severodvinsk city - Chetckaia, Svetlana (Tampereen ammattikorkeakoulu, 2017)
This project represents development of the idea for biogas production in Severodvinsk city on the Northern-West part of Russia. It includes research of important issues of the city infrastructure, opportunities for biogas production and application, economical evaluation and optimal scenario development. In Arkhangelsk region where Severodvinsk city is located, biogas production is not implemented, therefore current project is innovative. Challenging aspects of German experience transfer to a new region with different economical, legislative and climate background were defined and affected strategy adaptation. Based on the collected information, preliminary strategy of the project was created. Results from planning of technical aspects, substrate availability calculations and economical evaluation advanced the whole scenario. Conclusions for further steps for the project development were made and requirements for additional research were stated.